EXPERIMENTAL STUDY AND SEM ANALYSIS ON MORTAR CUBE WITH WOOD ASH FOR PARTIAL REPLACEENT OF CEMENT - Elangovan, G; Rajanandhini, V.M. (International Journal of Engineering Technologies and Management Research, 2018)
In the present view, several buildings are constructed ranging from ordinary residential building to sky - scrap structures. Invariably in all the structures, mortar plays a vital role in construction. Generally mortar is mixture of cement, fine aggregate, water and different type of admixtures used depends upon the situation. The cost of cement is increasing progressively day to day. In consequently cost of the building is also being increased. Wood ash does not make any pollution and eco – friendly for green building construction. This material is easily get more from burning of wood in home and industries, there by the cost of material too be reduced. Therefore, it has planned to conduct experiment on mortar in which the cement is partially replaced by wood ash. SEM Analysis is also carried out in mortar mix for observing bond between cement and wood ash.